Fusing Nanowires into Thin Films: Fabrication of Graded‐Heterojunction Perovskite Solar Cells with Enhanced Performance. Issue 22 (2nd May 2019) - Zhang, Yi; Yang, Hanjun; Chen, Min; Padture, Nitin P.; Chen, Ou; Zhou, Yuanyuan
Abstract: Perovskite solar cells (PSCs) have recently experienced a rapid rise in power conversion efficiency (PCE), but the prevailing PSCs with conventional mesoscopic or planar device architectures still contain nonideal perovskite/hole‐transporting‐layer (HTL) interfaces, limiting further enhancement in PCE and device stability. In this work, CsPbBr3 perovskite nanowires are employed for modifying the surface electronic states of bulk perovskite thin films, forming compositionally‐graded heterojunction at the perovskite/HTL interface of PSCs. The nanowire morphology is found to be key to achieving lateral homogeneity in the perovskite film surface states resulting in a near‐ideal graded heterojunction. The hidden role of such lateral homogeneity on the performance of graded‐heterojunction PSCs is revealed for the first time. The resulting PSCs show high PCE up to 21.4%, as well as high operational stability, which is superior to control PSCs fabricated without CsPbBr3 ‐nanocrystals modification and with CsPbBr3 ‐nanocubes modification. This study demonstrates the promise of controlled hybridization of perovskite nanowires and bulk thin films for more efficient and stable PSCs. Abstract : CsPbBr3 perovskite nanowires are incorporated into a bulk halide perovskite thin film based on solution processing. This method leads to a very uniform film surface region with optimized compositions and electronic structures, thereby enabling highly efficient and stable perovskite solar cells. This study points to a new direction of research in harnessing the interplay between perovskite nanocrystals and thin films.